Fabrication and characterization of natural origin chitosan‐ gelatin‐alginate composite scaffold by foaming method without using surfactant. Issue 4 (19th May 2012) - Sharma, Chhavi; Dinda, Amit Kumar; Mishra, Narayan Chandra
Abstract: A natural origin tripolymer scaffold from chitosan, gelatin, and alginate was fabricated by applying foaming method without adding any foam stabilizing surfactant. Previously, in foaming method of scaffold fabrication, toxic surfactants were used to stabilize the foam, but in this work, the use of surfactant has been avoided strictly, which can provide better environment for cellular response and viability. In foaming method, stable foam is produced simply by agitating the polymer (alginate‐gelatin) solution, and the foam is crosslinked with CaCl2, glutaraldehyde, and chitosan to produce tripolymer alginate‐gelatin‐chitosan composite scaffold. Microscopic images of the composite scaffold revealed the presence of interconnected pores, mostly spread over the entire surface of the scaffold. The scaffold has a porosity of 90% with a mean pore size of 57 μm. Swelling and degradation studies of the scaffold showed that the scaffold possesses excellent properties of hydrophilicity and biodegradability. In vitro cell culture studies by seeding L929 mouse fibroblast cells on scaffold revealed excellent cell viability, proliferation rate and adhesion as indicated by MTT assay, DNA quantification, and phase contrast microscopy of cell‐scaffold construct. The natural origin composite scaffold fabricated by the simplest method i.e., foaming method, but without adding any surfactant, is cheap, biocompatible, and it might find potential applications in the field of tissue engineering. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :